Determinants of Regionalism in the Collection of Stories by Helena Romer-Ochenkowska Tutejsi (1931) - Fedorovič, Irena; Davlevič, Miroslav (Slavistica Vilnensis, 2022)
The object of research is a collection of short stories by Helena Romer-Ochenkowska (1875–1947) titled Tutejsi (Warsaw 1931). It is the third series of short stories by a famous Vilnius writer, poet and journalist, which is devoted to regional issues. The protagonists of the stories are native inhabitants of the Lithuanian-Belarusian border, people of different nationalities (Poles, Belarusians, Lithuanians, Jews) and of various origins (wealthy and poor nobility, peasants, officials). The stories takes place during the years of World War I and in the interwar period, when some of the Lithuanian-Belarusian territories became part of the Second Polish Republic. The indigenous people of the borderland were shown in opposition to “strangers” – German soldiers and former Russian officials and clergy. The most important determinant of regionalism, as exemplified by the collection of Tutejsi stories, is linguistic distinctiveness, visible in the author’s narrative and in the characters’ individualized language. There are regionalisms and dialectisms in the language of the heroes typical of the North-Borderlands Polish language. Based on the methodology of cognitive linguistics, the authors of the article also distinguished several other concepts that characterize regionalism, which are: local territory / patriotism; landscape; customs / traditions; games / songs; costumes. The results of the research confirm the correctness of the scholars’ opinion that people of the borderland tend to position themselves as locals and maintain a sense of their own separateness.